Intro: Comparative Capitalism Research in Emerging Markets – A New Generation. Issue 4 (4th July 2021) - Wood, Geoffrey; Schnyder, Gerhard
ABSTRACT: In introducing this special section of New Political Economy, this paper explores the key themes that emerge from the three papers included in this special section presents a new generation of CC research in EMs which seeks to reconcile classical institutionalist approaches to capitalist variety with more recent attempts to shift back from supply-side to macroeconomic demand side factors, as well as brining the role of the state back in. This opening article summarises the key contributions we see emerging from this new generation of research and argues that it holds important lessons not just for the study of EMs but also advanced economies. We identify several important research questions for further research; but we also suggest that even the new approach that this new generation of CC research takes may not be enough to address the most pressing issue facing capitalist economies, namely the degradation of our natural environment.